Moral Values in the Short Story Collection Rasa Sayange by Nugroho Notosusanto and Its Feasibility as Teaching Material for Indonesian Literary Appreciation in High School: Nilai Moral dalam Kumpulan Cerpen Rasa Sayange Karya Nugroho Notosusanto dan Kelayakannya sebagai Bahan Ajar Pembelajaran Apresiasi Sastra Indonesia di SMA - Muhammad Zulfa Kertodirono; Sumartini (Anthology: Journal of Language, Literature, and Learning, 2025)
Short stories are not only entertainment for their readers, but can also be used as a learning tool. The values contained within them can be utilized by educators as teaching materials to develop students' character through literary appreciation learning by understanding the meaning and messages contained in a literary work. The objectives of this study are (1) to describe the moral values in the short story collection, and (2) to assess its feasibility as teaching material for Indonesian literature in high school. The approach used in this research is descriptive qualitative. While the method used is this analysis method. The data in this study are excerpts of sentences from the short story collection Rasa Sayange by Nugroho Notosusanto. The result of this study is an exposition of 7 moral values in the short story collection which include: (1) The value of honesty, (2) being oneself, (3) responsibility, (4) moral independence, (5) moral courage, (6) moral courage, and (7) being realistic and critical. The next result is the feasibility of the short story collection to be used as teaching material which includes: (1) Language aspect, (2) psychology aspect, and (3) cultural background aspect. For each of the moral values and feasibility aspects, the author provides 2 sentence excerpts as a reference.   Cerpen bukan hanya sebagai hiburan bagi pembacanya, tetapi juga dapat digunakan sebagai sarana belajar. Nilai nilai yang terkandung di dalamnya, dapat dimanfaatkan oleh pendidik sebagai bahan ajar untuk mengembangkan karakter peserta didik melalui pembelajaran apresiasi sastra dengan memahami makna dan pesan yang terkandung dalam sebuah karya sastra. Tujuan penelitian ini adalah (1) mendeskripsikan nilai moral dalam kumpulan cerpen, dan (2) mengkaji kelayakannya sebagai bahan ajar pembelajaran sastra Indonesia di SMA. Pendekatan yang digunakan dalam penelitian ini adalah deskriptif kualitatif. Sedangkan metode yang digunakan adalah metode analisis ini. Data dalam penelitian ini adalah kutipan kutipan kalimat dalam kumpulan cerpen Rasa Sayange karya Nugroho Notosusanto. Hasil dari penelitian ini adalah paparan 7 nilai moral dalam kumpulan cerpen yang meliputi : (1) Nilai kejujuran, (2) menjadi diri sendiri, (3) bertanggung jawab, (4) kemandirian moral, (5) keberanian moral, (6) keberanian moral, dan (7) realistik dan kritis. Adapun hasil yang berikutnya adalah kelayakan kumpulan cerpen untuk dijadikan sebagai bahan ajar yang meliputi : (1) Aspek bahasa, (2) aspek psikologi, dan (3) aspek latar belakang budaya. Masing masing dari nilai moral dan aspek kelayakan, penulis memberikan 2 kutipan kalimat sebagai acuan.